Herd Immunity VS Human Rights - Djamaludin Habi; Lisnawaty W. Badu; Jufryanto Puluhulawa3 (Universitas Negeri Gorontalo, 2021)
Abstract: This study aims to analyze law enforcement for people who refuse vaccination from the perspective of human rights, as well as to examine the obstacles faced by law enforcement in enforcing the law for people who refuse vaccination. This type of research is juridical empirical. The approach used in this research is the statute approach and the case approach. The analysis used in this study is descriptive data analysis using a qualitative approach to secondary data and primary data. The results show that the Government and the Covid-19 task force tend to provide education and rewards to people who want to be vaccinated and provide administrative sanctions for those who refuse, especially the space for movement and regulation of vaccine card requirements in receiving public services by the government and the police. The thing that hinders the process of vaccination to the public is the doubts that arise in the community about the safety and halalness of vaccines caused by hoax news from sources that are not credible.